Pengaruh Volume Pemberian Air terhadap Pertumbuhan Tiga Varietas Tomat (Lycopersicum esculentum Mill) - Roffiul Umamil Marzukoh; Amalia Tetrani Sakya; Muji Rahayu (Agrosains : Jurnal Penelitian Agronomi, 2013)
Tomato is one of the agriculture commodity that has many benefits. However, the production of tomato in in low land is still low so it needs effort to increase production. Issues that facing in low land cultivation are high temperature and uncertain water availibility. This study aimed to investigate the effect of watering volume on growth of tomato. This research was conducted at the Greenhouse and Laboratory of Plant Fisiology and Biotechnology, Faculty of Agriculture, Sebelas Maret University. Research was conducted from December 2012 to May 2013. This research used completely randomized factorial design with two factors of treatment, namely variety of tomato were Opal, Gondol and Mutiara and watering volume (4,4 l, 3,42 l, 2,34 l, and 1,28 l in each watering). Data were analyzed by analysis variance and continued by Duncan Multiple Range Test level of 5%. The results showed that the higher of watering volume increases the growth of tomato. Plant height, number of branch, leaf area, dry weight of shoot, dry weight of root and the length of root increase with increasing watering volume. The appropriate tomato that can be developed in the various watering is Gondol.